2017
DOI: 10.1002/14651858.cd006095.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics for the prevention of Clostridium difficile-associated diarrhea in adults and children

Abstract: Probiotics for the prevention of Clostridium difficile-associated diarrhea in adults and children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
241
0
8

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 346 publications
(278 citation statements)
references
References 136 publications
4
241
0
8
Order By: Relevance
“…Limited evidence supports the use of probiotics to decrease recurrence of CDI, and no effective immunotherapy is currently available 205 . Faecal microbiota transplantation (FMT) is a highly effective rescue treatment and should be considered in patients who have had >2 recurrences, as the efficacy of antibiotics in these patients is ~30%.…”
Section: Managementmentioning
confidence: 99%
“…Limited evidence supports the use of probiotics to decrease recurrence of CDI, and no effective immunotherapy is currently available 205 . Faecal microbiota transplantation (FMT) is a highly effective rescue treatment and should be considered in patients who have had >2 recurrences, as the efficacy of antibiotics in these patients is ~30%.…”
Section: Managementmentioning
confidence: 99%
“…36 A recent Cochrane review that specifically analyzed the effect of probiotics in preventing CDAD included 3 studies on children (n = 605) and reported a relevant effect in children receiving probiotics (RR 0.37; 95% CI, 0.23-0.60). 33 Many different probiotic strains were tested and a conclusive recommendation on the most effective treatment to prevent CDAD was not released. The authors concluded that further head-to-head trials aimed at identifying optimal strains and dosages are needed for this purpose.…”
Section: Preventionmentioning
confidence: 99%
“…Use of probiotics might be helpful in primary prevention 4142. However, US guidelines do not recommend their use outside clinical trials because of insufficient data 6…”
Section: How Can We Reduce the Risk Of C Difficile Infection?mentioning
confidence: 99%